Inflammatory markers in peripheral blood in patients with asthma - Dimitrievska D; Zdraveska M; Dejan Todevski; Monika Tushevska Mitkovska; Nikola Chamurovski (My University, 2020)
Asthma is one of the most common chronic diseases all over the world, resulting from a state of persistent sub-acute inflammation of the airways. The main attribute of asthma is inflammation, which leads to airway remodeling, bronchial hyper-reactivity and reversible or partly reversible airway obstruction. Asthma is a chronic inflammatory disorder of the airways in which many cells and inflammatory mediators play a role. (GINA). Many cells and mediators take part in creating the asthmatic inflammatory reaction, but eosinophils play a central role. All of the inflammatory cells and mediators can be detected in the airflow tissue. Some of them can be detected in the asthmatics peripheral blood too. This study includes 30 patients of the Pulmology and Allergy Clinic, Skopje, with confirmed bronchial asthma, treated with ICS. In all of the patients we followed Eo count, ECP and IL-5 in peripheral blood at the beginning of the study, after 2 and 6 months treatment. Following the parameters during treatment with ICS we registered changes in all of the tested parameters. Our conclusion is that the ICS objectively suppress the inflammatory reaction in asthma and the biologic markers (IL-5, Eo and ECP), which we have followed, can measure the accomplished effect. They could be used in every day practice, not only as diagnostic parameters but also as valid therapeutic guides in the treatment of asthma
Keywords: asthma; treatment; Eo count; ECP; IL-5